Comprehensive Analysis of Phytoestrogens Intervention in Osteoporosis Management: A Systematic Review of Randomized Controlled Trials - Widowati, Ayu Rizky (Asian Journal of Health Research, 2023)
Introduction: Osteoporosis is a medical condition characterized by increased bone turnover and decreased bone mass, which leads to bone fractures. Antiresorptive therapy, hormone replacement therapy (HRT), and bisphosphonates are used as first-line therapy related to numerous side effects. The osteoprotective properties of phytoestrogens are well known. This systematic review aims to explore the potential of phytoestrogen in the management of osteoporosis patients based on serum bone biomarker analysis. Methods: The literature search was conducted in six databases. The outcome of interest measures the mean changes in bone mineral density (BMD) and other serum bone biomarkers. Various forms of phytoestrogen intervention were used, including isoflavone extracts with an administered dose (tablets, capsules), genistein extract (tablets), resveratrol, and isolated soy protein (IBS) in powder form, beverages, food and snacks, and soy products. Quality appraisal was done using the Cochrane Risk of Bias Tool 2. Ten articles were included in the systematic review. Results: Seven studies found the mean changes in BMD values were significantly higher than the control group's after phytoestrogen intervention. Phytoestrogens dramatically boost numerous bone formation markers, including calcium, phosphorus, Ca/P ratio, and vitamin D, followed by a drop in BAP and osteocalcin levels. Phytoestrogens dramatically increased numerous bone formation markers, including calcium, phosphorus, Ca/P ratio, and vitamin D, followed by a decrease in BAP and osteocalcin levels. Furthermore, intervention may reduce bone resorption indicators such as CTX, RANKL, AKP, OPG, DPD, and PTH. Conclusion: Phytoestrogen intervention has demonstrated effectiveness in increasing bone mineral density and serum bone biomarkers.